Angular Vessels for Free‐Tissue Transfer in Head and Neck Reconstruction: Clinical Outcomes. (19th February 2020) - Hanick, Andrea; Ciolek, Peter; Fritz, Michael
Abstract : Objectives/Hypothesis: To evaluate the efficacy and reconstructive applications of angular vessel microvascular anastomosis in free‐tissue transfer. Study Design: Retrospective cohort study. Methods: A study of patients treated from January 2010 to July 2017 was performed. Four hundred thirty patients undergoing free‐tissue transfer at the Cleveland Clinic by a single reconstructive surgeon were reviewed. Patients in whom free‐tissue transfer was performed using angular vessels were included. Patients in whom free‐tissue transfer was performed using another vascular supply of the head and neck were excluded. Primary outcome was free‐flap failure. Secondary outcomes included other postoperative complications and hospital length of stay. Results: Thirty‐one patients underwent free‐tissue transfer with microvascular anastomosis to the angular vessels during the study period. Seventy‐one percent of patients underwent reconstruction immediately following tumor ablation. A variety of primary subsites were reconstructed; 58% underwent nasal reconstruction, 16% orbit/skull base reconstruction, 13% palatal reconstruction, 6% maxillary reconstruction, and 6% mandible reconstruction. Eighty‐seven percent of patients underwent free‐tissue transfer from an anterolateral thigh donor site. Ninety‐seven percent of patients had successful free‐tissue transfer with a viable flap during the follow‐up period; only one patient experienced flap failure attributed to vascular insufficiency. Average length of stay was 4.7 days, and the most common length of stay was 3 days. Conclusions: The angular vessels provide excellent arterial supply and venous drainage to serve as a viable option for microvascular anastomosis during free‐tissue transfer for head and neck reconstructive surgery. They are an ideal vascular source for central face and skull base reconstruction. Level of Evidence: NA Laryngoscope, 130:2589–2592, 2020